Evaluation of PPAR gamma agonists: A molecular docking and QSAR study of chalcone analog - Ruchita N. Pingale, Kumar Pratyush, Bhaveshwari Wagh, Ankita A. Jain, Raghu Prasad Mailavaram (Journal of Applied Pharmaceutical Science, 2025)
In recent years, chalcones have attracted researchers with their unique structure and promising potential across a wide range of scientific disciplines. They are naturally occurring 1,3-diphenyl-2-propen-1-ones. As well as regulating cell proliferation, differentiation, and angiogenesis, PPARs are also involved in cell differentiation. The present study evaluates the molecular activity of 60 chalcone analogs and two marketed drugs as potential PPAR gamma agonists. Molecular docking studies, structural property calculations, and 2D QSAR studies were carried out to screen the best molecule in the library. The compound coded with 2i was found to have the highest binding affinity and selectivity for PPAR gamma. Firm interactions within 5.0 Å were considered for the docking analysis. Ramachandran plot interpretations also helped us to justify the firm binding at the catalytic site. The correlational studies using the QSAR model were carried out, and the coefficient of regression was found to be 0.9247, and the results were plotted. The 2i was found to be the most suitable compound from the library.
Keywords: Chalcone, molecular docking, PPAR gamma, QSAR, structural property calculation